Consensus Recommendations for the Diagnosis and Management of X-Linked Hypophosphatemia in Belgium - Laurent, Michaël R.; De Schepper, Jean; Trouet, Dominique; Godefroid, Nathalie; Boros, Emese; Heinrichs, Claudine; Bravenboer, Bert; Velkeniers, Brigitte; Lammens, Johan; Harvengt, Pol; Cavalier, Etienne; Kaux, Jean-François; et al. (Frontiers in Endocrinology, 2021)
X-linked hypophosphatemia (XLH) is the most common genetic form of hypophosphatemic rickets and osteomalacia. In this disease, mutations in the PHEX gene lead to elevated levels of the hormone fibroblast growth factor 23 (FGF23), resulting in renal phosphate wasting and impaired skeletal and dental mineralization. Recently, international guidelines for the diagnosis and treatment of this condition have been published. However, more specific recommendations are needed to provide guidance at the national level, considering resource availability and health economic aspects. A national multidisciplinary group of Belgian experts convened to discuss translation of international best available evidence into locally feasible consensus recommendations. Patients with XLH may present to a wide array of primary, secondary and tertiary care physicians, among whom awareness of the disease should be raised. XLH has a very broad differential-diagnosis for which clinical features, biochemical and genetic testing in centers of expertise are recommended. Optimal care requires a multidisciplinary approach, guided by an expert in metabolic bone diseases and involving (according to the individual patient’s needs) pediatric and adult medical specialties and paramedical caregivers, including but not limited to general practitioners, dentists, radiologists and orthopedic surgeons. In children with severe or refractory symptoms, FGF23 inhibition using burosumab may provide superior outcomes compared to conventional medical therapy with phosphate supplements and active vitamin D analogues. Burosumab has also demonstrated promising results in adults on certain clinical outcomes such as pseudofractures. In summary, this work outlines recommendations for clinicians and policymakers, with a vision for improving the diagnostic and therapeutic landscape for XLH patients in Belgium.